Multi-criteria group decision making methods using AHP and integrated Web-based decision support systems - Ozer, Ibrahim (University of Ottawa (Canada), 2007)
This thesis explores different group decision making methods using the Analytical Hierarchical Process (AHP) applied to the multi-criteria decision making problem of selecting a preferred "site" and develops a support system for group decision making. The group members consider sites to have alternative and often conflicting uses. It is imperative for decision makers in the responsible group to have an appropriate combination of tools, computer software and decisions support systems in order to make the most preferred decisions as a group despite potential inherent conflict among members of the decision making group. To support this idea and facilitate decision making, alternative group multi-criteria decision making (MCDM) evaluation techniques are examined. These include; AHP, Weighted Sum Method (WSM), Weighted Product Method (WPM), AHP Combined Method, Group Evaluation Method, Fuzzy AHP, Fuzzy AHP Combined, and Fuzzy AHP Group. A web-based comparison framework is developed as a prototype to facilitate model use. These methods are applied to the evaluation of coastal zone sites for alternate marine use including aquaculture or fish farming. Aquaculture is one of the fastest growing activities among coastal nations. At the same time, companies, researchers, and coastal communities are seeking assistance in identifying appropriate coastal zone sites for commercial fishing and aquaculture activities, habitat reserves, and marine recreation. The aquaculture case study evaluates four possible fish sites in the Grand Marian Island area of Atlantic Canada.
Keywords: Engineering, System Science.